The Role of Woman on Household Food Security in Sleman Daerah Istimewa Yogyakarta - Vini Arumsari (Economic Journal of Emerging Markets, 2008)
The objectives of this research are (1) to know the diversification design of food material in household level, (2) to analyze the factors that influenced the role of female in food diversification for food security reason in household level and (3) to analyze the factors that influenced the diversification design of food material in household level.The method of this research is descriptive method with the case study at Sleman Regency, Yogyakarta Special Region Province. The primary data is collected from 50 respondents of female in household level using the simple random sampling and the regression analyze with Ordinary Least Square (OLS) method is applied for the data analysis.The result shows that the diversification design of food material in household level is mainly the rice paddy which is followed by potatoes, noodles, wheat and corn. The main  factors that influence the role of female in food diversification for food security is the household income and the numbers of family dependent. Furthermore, the factors that determine the diversification design of food material are household income, product image and the number of family dependent.     Keywords: role of female, food diversification, food security, household level